Encapsulation of Essential Oils Using Complex Coacervation: A Study on Microcapsule Formation and Efficiency - Evcin, Atilla; Enginar, Hüseyin; Ersoy, Bahri; Duman, Erman; Kayhan, Hülya; Çetinkaya, Zeynep (International Journal of Computational and Experimental Science and Engineering, 2024)
Encapsulation by Coacervation is a process used to create microcapsules. Coacervation is a process that has been used in the food and pharmaceutical industry to produce microspheres with an active ingredient, such as drugs, flavors or fragrances encapsulated by them. It is common in pharmacies, food preparation, cosmetics, and agriculture. This phase separation process is called Coacervation, where a colloidal (in this case polymer) solution will separate into two distinct liquid phases: a Polymer-rich phase, which we refer to as the coacervate, and the other is known as Polymer-poor or solvent-based. This can be accomplished by varying the temperature or pH of a non-solvent being introduced. In this study, essential oils of lemon and eucalyptus were encapsulated by the complex coacervation process using gum Arabic, gelatin, and chitosan as wall materials. Glutaraldehyde was used as a cross-linking agent in the methodology. FT-IR and GC characterized the essential oils used. The microcapsules were analyzed using a digital microscope, scanning electron microscopy (SEM), and thermogravimetric analysis. Conclusively, microcapsules were formed in spherical form. Encapsulation efficiencies were obtained between 75-78%. In conclusion, microencapsulated essential oils offer a technology that makes essential oils more effective, long-lasting, and customized. These advantages reveal their widespread impact, offering various uses for a variety of industries and applications.